ASSESSMENT OF THE INFLUENCE OF BIOMETRIC FEATURES OF THE EYE ON THE SUCCESS OF OPERATION IN HORIZONTAL STRABISMUS - Farzieva, M.S. (World of Medicine and Biology, 2024)
In the course of this study, a comprehensive clinical, laboratory and instrumental prospective examination of 28 patients aged 1.0 to 38.0 years (mean age 7.79±7.43 years) with horizontal strabismus was conducted at the Batygoz Clinic in 2022-2023. Patients were divided into 3 groups: esotropia (n=9, 32.1 %), exotropia (n=8; 28.6 %) and infantile esotropia (n=11; 39.3 %), as well as into 3 age groups according to the type of postoperative deviation, development of the eyeball and binocularity. It was found that the distance to the limbus (d), the width of the attachment of the internal rectus muscle (a, b, c) positively correlated with the likelihood of surgical success (p=0.058; p=0.026; p=0.019; p=0.058). On the other hand, the axial length and the angle of strabismus for near vision were negatively correlated with the probability of surgical success (p=0.031; p=0.021). It was found that the axial length and anatomy of the extraocular muscles are among the factors influencing the success of surgical intervention for horizontal strabismus.
Keywords: strabismus; horizontal strabismus; biometric examination; esotropia; exotropia; infantile esotropia; postoperative abnormalities